Basic Flight Physiology - Reinhart, Richard O. (McGraw-Hill, 2008)
Covers the many factors that can affect 'medical airworthiness'. This book includes medical developments that have a bearing on cockpit health. It provides accident-preventing information you can use to anticipate and compensate for the physiological effects of flying that can erode performance.